Systematic screening for k type phase transitions – general approach and positive example for a binuclear Cu(ii) paddlewheel structure. Issue 4 (21st December 2020) - Strothmann, Robert; van Terwingen, Steven; Kalf, Irmgard; Englert, Ulli
Abstract : How to screen for k type phase transitions? Pseudo symmetry in reciprocal space represents a successful answer. Abstract : Continuous structural phase transitions associated with a loss of translational symmetry, so called klassengleiche or k type phase transitions, are less obvious to detect than their t type counterparts: in contrast to the latter, they result in the formation of antiphase domains and remain invisible to standard X-ray diffraction experiments. The low symmetry and low temperature phase may, however, retain traces of the lost translational symmetry in terms of pseudo symmetry which is reflected as pseudo translation in the diffraction pattern. We exploited this tendency and screened more than 100 000 deposited structures in reciprocal space for pseudo symmetry. This automatic test was followed by a check in real space which required human intervention to avoid false positives as a result of apparent extra symmetry in the electron density distribution. As a proof of principle, we applied our two step strategy to a small number of synthetically affordable compounds for which only low temperature diffraction data were available. For a dinuclear carboxylato-bridged Cu(ii ) paddlewheel structure [P. Smart et al., CrystEngComm, 2013, 15, 3160] we were able to collect temperature-dependent diffraction data and confirm the existence of a k phase transition at ca. 230 K. Upon cooling, crystallographic symmetry of the parent space group turns into pseudo symmetry in the subgroup.